Voters response to public information disclosure policies in the local head election of Ciamis Regency 2024 - Endah, Kiki; Nursetiawan, Irfan; Vestikowati, Endah (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
The lack of political education for the people of Ciamis Regency in local head elections has an impact on the lack of voter information on local head candidates, so that political behavior is based on assumptions and non-rational factors. Voters are vulnerable to negative influences in the local head election process and are rooted in political fraud at the grassroots. This study aims to determine Voters response to public information disclosure policies in the local head election of Ciamis Regency 2024. The research method uses qualitative research with an explanatory approach. The results showed that the level of community response in Ciamis Regency in the pre-election process of local head elections was quite high, as evidenced by the many positive comments and the enthusiasm of the community to express their opinions on social media platforms regarding candidates for Regent and Deputy Regent in the 2024 local head elections. Furthermore, to increase voter participation in future local head elections, the General Election Commission of Ciamis Regency must increase the intensity of socialization, political education, and conduct extensive social media monitoring.